2015
DOI: 10.1160/th14-10-0834
|View full text |Cite
|
Sign up to set email alerts
|

Pro-oxidant HDL predicts poor outcome in patients with ST-elevation acute coronary syndrome

Abstract: Oxidative stress affects clinical outcome in patients with ST-elevation acute coronary syndrome (STE-ACS). Although high-density lipoprotein (HDL) particles are generally considered protective, deleterious properties of HDL have been observed in patients with acute myocardial infarction. Here, we analysed the association between pro-oxidant HDL and all-cause mortality in STE-ACS patients. We determined the antioxidant function of HDL in 247 prospectively enrolled patients undergoing primary percutaneous corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…So far, antioxidative properties of HDL have been found impaired in common CHF‐related comorbidities such as chronic kidney disease and type 2 diabetes mellitus, and determination of the HOI turned out to be a useful predictor of cardiovascular events and mortality in patients with acute coronary syndrome . With respect to CHF, a previously conducted case‐control study has reported reduced HDL antioxidative capacity in patients with ischemic CHF .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…So far, antioxidative properties of HDL have been found impaired in common CHF‐related comorbidities such as chronic kidney disease and type 2 diabetes mellitus, and determination of the HOI turned out to be a useful predictor of cardiovascular events and mortality in patients with acute coronary syndrome . With respect to CHF, a previously conducted case‐control study has reported reduced HDL antioxidative capacity in patients with ischemic CHF .…”
Section: Discussionmentioning
confidence: 99%
“…Samples were stored at −80°C and used for further analyses immediately after thawing. HDL antioxidative capacity, the ability of HDL to inactivate previously oxidized LDL, was measured using a well‐validated cell‐free assay comparable to the cell‐based assays as previously described . The assay is based on the conversion of 2′,7′‐dichlorodihydrofluorescein diacetate (DCF) into its fluorescent form in the presence of oxidized LDL.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations